Manipulation of the anoxic metabolism in escherichia coli by ArcB deletion variants in the ArcBA two-component system - Bidart, G.N. (2012)
Bioprocesses conducted under conditions with restricted O2 supply are increasingly exploited for the synthesis of reduced biochemicals using different biocatalysts. The model facultative anaerobe Escherichia coli has elaborate sensing and signal transduction mechanisms for redox control in response to the availability of O2 and other electron acceptors. The ArcBA two-component system consists of ArcB, a membrane-associated sensor kinase, and ArcA, the cognate response regulator. The tripartite hybrid kinase ArcB possesses a transmembrane, a PAS, a primary transmitter (H1), a receiver (D1), and a phosphotransfer (H2) domain. Metabolic fluxes were compared under anoxic conditions in a wild-type E. coli strain, its ΔarcB derivative, and two partial arcB deletion mutants in which ArcB lacked either the H1 domain or the PAS-H1-D1 domains. These analyses revealed that elimination of different segments in ArcB determines a distinctive distribution of D-glucose catabolic fluxes, different from that observed in the ΔarcB background. Metabolite profiles, enzyme activity levels, and gene expression patterns were also investigated in these strains. Relevant alterations were observed at the P-enol-pyruvate/pyruvate and acetyl coenzyme A metabolic nodes, and the formation of reduced fermentation metabolites, such as succinate, D-lactate, and ethanol, was favored in the mutant strains to different extents compared to the wild-type strain. These phenotypic traits were associated with altered levels of the enzymatic activities operating at these nodes, as well as with elevated NADH/NAD+ ratios. Thus, targeted modification of global regulators to obtain different metabolic flux distributions under anoxic conditions is emerging as an attractive tool for metabolic engineering purposes. © 2012, American Society for Microbiology.